Catecholamine-induced myocardial fibrosis and oxidative stress is attenuated by Terminalia arjuna (Roxb.) - Kumar, Santosh; Enjamoori, Rajesh; Jaiswal, Amardeep; Ray, Ruma; Seth, Sandeep; Maulik, Subir Kumar (Journal of pharmacy and pharmacology, 2009)
Myocardial fibrosis and oxidative stress accompany a number of cardiac disorders such as hypertrophic cardiomyopathy, hypertensive heart disease and cardiac failure. Stem bark of Terminalia arjuna has been advocated for cardiac ailments. The present study evaluated the effects of T. arjuna bark extract on myocardial fibrosis and oxidative stress induced by chronic beta-adrenoceptor stimulation. Aqueous extract of T. arjuna bark was evaluated at 63, 125 and 250 mg/kg given orally for antifibrotic and antioxidant effects in rats given the selective beta-adrenoceptor agonist isoprenaline (5 mg/kg s.c.) for 28 days. Captopril (50 mg/kg per day, given orally), an inhibitor of angiotensin-converting enzyme used as a standard cardioprotective drug, was used as a positive control. Isoprenaline caused fibrosis, increased oxidative stress and cardiac hypertrophy (increased heart weight : body weight ratio and cardiomyocyte diameter). The T. arjuna bark extract and captopril significantly prevented the isoprenaline-induced increase in oxidative stress and decline in endogenous antioxidant level. Both also prevented fibrosis but not the increase in heart weight : body weight ratio. T. arjuna protects against myocardial changes induced by chronic beta-adrenoceptor stimulation.